Group Counseling Services as an Effort to Increase Students Confidence in Speaking English: Literature Review - Frimaulia, Sara; Alwina, Sakura (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study aims to examine the role of group counseling services in increasing students' confidence in speaking English. This study uses a qualitative approach with a literature study type of research. Literature study is a method of collecting data through an in depth review of relevant literature and theories. The data sources used in this study are scientific journal articles. Data collection was carried out through documentation studies and literature searches with the following steps: (a) determining search keywords such as group counseling, self confidence, English speaking skills, group guidance and counseling, and student self confidence, (b) searching scientific literature using online databases such as Google Scholar, Research Gate, ERIC (c) selecting and selecting relevant sources based on eligibility criteria, namely sources published in the last five to ten years, scientific in nature, and directly related to the research topic, and (d) recording and classifying the findings according to the discussion theme, for example group counseling theory, factors that influence self- confidence, and empirical findings on the application of group counseling in English learning. The data analysis technique used is content analysis. The analysis steps include: (a) data reduction, (b) data classification, (c) data interpretation, and (d) drawing conclusions. The results of this study indicate that group counseling services have an important role in increasing students' confidence in speaking English through the process of social interaction, self reflection, and emotional support between group members. The dynamics formed in counseling activities help students overcome anxiety, embarrassment, and fear of speaking in public, while also fostering courage to express opinions.